Nanowired delivery of drugs and antibodies for neuroprotection in brain diseases with co-morbidity factors - Sharma, Hari Shanker; Wiklund, Lars; Sharma, Aruna (International review of neurobiology, 2023)
Nanowired Delivery of Drugs and Antibodies for Neuroprotection in Brain Diseases with Co-morbidity Factors, Volume 171 in the International Review of Neurobiology series, highlights new advances in the field with this new volume presenting interesting chapters on Neurodegenerative diseases, Stress induced exacerbation of Alzheimer's disease brain pathology is thwarted by co-administration of nanowired cerebrolysin and amyloid beta peptide antibodies with serotonin 5-HT6 receptor antagonist SB-39988, Nanowired delivery of dl-3-n-butylphthalide with antibodies to alpha synuclein potentiated neuroprotection in Parkinson's disease with emotional stress, Efficacy of invasive and non-invasive methods for the treatment of Parkinson?s disease: nanodelivery and enriched environment, and much more. Other sections cover Sleep deprivation induced exacerbation of Parkinson's disease pathophysiology is attenuated by co-administration of nanowired cerebrolysin and serotonin-3 receptor antagonist ondansetron, Co-administration of DL-3-n-butylphthalide and neprilysin is neuroprotective in Alzheimer disease associated with brain injury, Stress and brain diseases, Pathophysiology of sleep deprivation enhances amyloid beta peptide and p-tau in the CSF and brain, Neuroprotective effects of nanowired delivery of multimodal drug cerebrolysin and monoclonal 5-HT antibodies, Prior heat exposure exacerbates brain blast injury, Neuroprotection by nanodelivery of cerebrolysin with serotonin 6 receptor antagonist SB-399885, the Effects of curcumin nanodelivery on several brain pathologies, and more.